Teleworking in times of COVID-19 - Ramos, Valentina; Ramos-Galarza, Carlos; Tejera, Eduardo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
COVID-19 as a global pandemic had consequences at the health level, but also at the social level, since as a consequence of preventing its spread, governments took measures that affected work, adopting teleworking as an alternative to be able to continue with work activities from home. This study analyzes the characteristics of teleworking and its impact on the perception of productivity and well-being of people who are in social isolation due to COVID-19. The study was conducted in Ecuador, in a sample of 459 people who answered an online questionnaire. The results found show that there are aspects that affect productivity, such as working long hours, personal skills, specifically self-motivation and organizational skills, and mental health. With this research, a better understanding of the situation of teleworking in confinement due to COVID-19 is achieved, allowing both individuals and organizations to develop resources so that work from home is successful and people feel satisfied while this situation lasts